2016
DOI: 10.1159/000447325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Frequency Repetitive Transcranial Magnetic Stimulation on Cerebral Hemodynamics in Patients with Disorders of Consciousness: A Sham-Controlled Study

Abstract: Objective: This study aimed to determine the effects of high-frequency repetitive transcranial magnetic stimulation (rTMS) on cerebral hemodynamics in patients with disorders of consciousness (DOC). Methods: In this sham-controlled study, 20-Hz and sham rTMS were applied over the left primary motor cortex (M1) of 5 patients in a vegetative state (VS) and 5 patients in a minimally conscious state (MCS). The clinical behavior and cerebral blood flow (CBF) velocity in the bilateral middle cerebral artery (MCA) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…Neuroimaging data also showed changes of the blood-oxygenlevel-dependent signal [65] and cerebral blood flow [66] after rTMS of the premotor or motor cortex. MCS patients showed significant increases in cerebral blood flow, which were temporally related to high-frequency rTMS [67]. Our recent studies also added evidence to the case for rTMS as an effective neuromodulation tool by quantitative EEG [68] and TMS-EEG analysis [69].…”
Section: Repetitive Transcranial Magnetic Stimulationsupporting
confidence: 57%
“…Neuroimaging data also showed changes of the blood-oxygenlevel-dependent signal [65] and cerebral blood flow [66] after rTMS of the premotor or motor cortex. MCS patients showed significant increases in cerebral blood flow, which were temporally related to high-frequency rTMS [67]. Our recent studies also added evidence to the case for rTMS as an effective neuromodulation tool by quantitative EEG [68] and TMS-EEG analysis [69].…”
Section: Repetitive Transcranial Magnetic Stimulationsupporting
confidence: 57%
“…However, at the group level, no behavioral enhancements were noticed in any of the RCTs when applied over M1. 45,46,48 Future RCTs should target the DLPFC, similarly to tDCS, as two uncontrolled observational rTMS studies show some positive effects. 50,51 Demographic and clinical characteristics of responders should also be investigated in larger RCTs or meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…45 The second RCT trial reported no behavioral improvement after one session of M1 20Hz rTMS for ~10 minutes in 10 patients with DOC (1-26 months post-onset) but improved hemodynamic functions (i.e., cerebral blood flow velocity) in the MCS as compared to the UWS group. 46 5-Hz rTMS was applied on M1 for ~7 minutes in a third RCT in 5 UWS and 5 MCS patients (5-23 months post-injury) evaluating its effects on sleep-wake cycles. 47 Even if there was no behavioral effect reported, significant rTMS after-effects regarding the slow wave activity power were detected in the MCS but not in the UWS group.…”
Section: Repeated Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…Sham stimulation was delivered using the same protocol except that the angled coil was positioned away from the head. Thus, the magnetic field could not penetrate the brain, although the acoustic artefact of real stimulation was reproduced in the sham rTMS [ 20 ].…”
Section: Methodsmentioning
confidence: 99%